The biology of Canadian weeds. 120. Neslia paniculata (L.) Desv. - Francis, A.; Warwick, S. I. (Canadian Journal of Plant Science, 2003)
A review of biological information is provided for Neslia paniculata. Native to central Eurasia, this species is naturalized in other temperate regions of the northern hemisphere. In North America it is most abundant in Canada’s prairie provinces, but has spread west and north to British Columbia, Alaska, Yukon and the Northwest Territories, and to scattered locations in eastern Canada and the northern United States. It is typically a summer annual weed of disturbed soils. Its growth habit and persistence in the seed bank have enabled it to spread as an adventive and to maintain its presence in cultivated areas. While it is present in relatively low frequency as a weed in most crops, its indehiscent seed pods can contaminate harvested crops and spread in seed commodities. The small size of its seed pods and the similarity of its seeds to those of canola and condiment mustard have led to its regulation as a significant contaminant of commercial seed. It is generally well controlled by herbicides (e.g., sulfonylureas, glyphosate, MCPA, bromoxynil, and 2, 4-D); however, a population resistant to metsulfuron-methyl, one of the Group 2 herbicides that inhibit acetolactate synthase (ALS), was found at a site in Alberta in 1998. Key words: Ball mustard, Neslia paniculata, weed biology, herbicide resistance, seed contaminant